Research in Language Education Context - Kaharuddin, Kaharuddin (Westscience Press, 2025)
Research in the scientific area of language (e.g. linguistics, literature, and language education) has been carried out by many language practitioners in Indonesia, but few know clearly the focus areas of research in these branches of the language sciences. This paper aims to provide a comprehensive explanation of three things: first, research in the context of language education; second, to provide a clear and concise overview of the scientific area of focus in language education research; third, to justify the rationale for the need to conduct research in the area of language education. To achieve those objectives, the author has conducted a literature study by reading various references in the form of books and scientific articles. The results of the study show that the area of language research is basically divided into two scientific disciplines, namely linguistics and literature. Each of these scientific domains has its own branches consisting of sub-disciplines as the focus of research. Furthermore, language education research is identified as being in the linguistics area in the applied linguistics discipline consisting of 10 sub-focus research objects. This information is believed to be used as a basis and also a reference to clearly identify the scope of language education research conducted by researchers in the area of language education.